Sosialisasi dan Edukasi Makanan Sehat untuk Jajan Sekolah Kepada Siswa Siswi di SD Muhammadiyah Bligo 01 - septian, ivan; Dhims Abdi Perdana; Muhammad Adiansyah; Mega Widya Putri (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
healthy snacks in the school environment to improve students' eating patterns. Through a qualitative approach, this research includes a survey of the types of healthy snacks available, students' responses to these changes, and their impact on health and academic performance. The research results show that the implementation of healthy snacks in schools makes a positive contribution to students' lifestyles, creates awareness of nutrition, and supports the formation of healthy eating habits from an early age.s